Influência da suplementação de tomate e licopeno na remodelação cardíaca após infarto agudo do miocárdio - Pereira, Bruna Letícia Buzati [UNESP] (2015)
Introduction: Heart failure is a common complication after the acute myocardial infaction (AMI), and cardiac remodeling has a prominent role in this scenario. Increased oxidative stress and inflammation are associated with cardiac remodeling after AMI. Due to the great economic and social and high mortality rates, it's important to identify other factors that modulate the process of cardiac remodeling and among this factors are the supplementation of foods with antioxidant properties, such as tomato (Lycopersicon esculentum), and of its primary constituents, the lycopene. Objectives: Evaluate the influence of tomato and lycopene supplementation in cardiac remodeling after AMI. Methods: Male Wistar rats, weighing between 200 and 250g, were submitted to the experimental infarction or sham surgery and divided into six groups: 1) Sham group (animals undergoing sham surgery) fed a standard diet (SC group); 2) Sham group fed diet supplemented with 1 mg lycopene/kg body/day (SL group); 3) Sham group fed diet supplemented with tomato (ST group); 4) infarcted group (animals submitted to experimental infarction) fed a standard diet (IC group); 5) infarcted group fed diet supplemented with 1 mg lycopene/kg of body weight/day (IL group); 6) infarcted group fed diet supplemented with tomato (IT group). The lycopene and the tomato were dilute in corn oil to be add into the diet (0.5 ml of corn oil/kg body weight/day) and the standard group received the same oil. After three months of observation the animals underwent functional, morphometric and biochemical analysis. The values were expressed as mean ± standard deviation. The variables that did not meet the criteria of normality and equal variance were normalized before analysis. Comparisons between groups were made by two-way analysis of variance (ANOVA). For non-normalized data, we used Kruskal-Wallis test (comparison between the Sham groups, SC, SL and ...